The CT and MR evaluation of lissencephaly. - Byrd, S E; Bohan, T P; Osborn, R E; Naidich, T P (American Journal of Neuroradiology, 1988)
Lissencephaly is a rare congenital malformation of the brain that has characteristic radiographic and clinical findings. Fifteen cases of lissencephaly were studied with CT and/or MR, and a classification was developed based on these cases and the description of this abnormality found in the literature. These findings can be divided into two groups, primary and secondary. The primary findings consist of (1) a cerebral surface that is agyric or agyric with pachygyric areas, (2) a cerebral contour that is oval or "hourglass" due to lack of or incomplete opercularization of the brain, and (3) an abnormal gray-white-matter distribution in the cerebral hemispheres. The primary findings are necessary to make the diagnosis, which can be made with either CT or MR; however, MR provided better delineation than CT of the cerebral surface and contour as well as better gray-white-matter differentiation in the lissencephalic brains. We believe MR is the technique of choice for evaluating patients with lissencephaly because it is safer and more versatile than CT and provides better delineation of the brains of children.